Alternative Action Organizations: Social Solidarity or Political Advocacy?. (May 2018) - Giugni, Marco; Grasso, Maria
This article investigates the involvement of alternative action organizations in three forms of political advocacy in an attempt to gauge their degree of politicization. These forms can be understood as representing three different ways of making political claims: by raising public awareness with respect to a given cause or issue, by trying to influence the policy maker through "insider" lobbying activities, and by protesting in the streets as "outsiders." Our findings show strong cross-national variations in all three forms of political activities, although not always following a consistent pattern. They also suggest that there is a relationship between the severity of the economic crisis and the form of advocacy. Most important, our analysis suggests that the politicization of alternative action organizations depends both on certain internal characteristics such as their degree of formalization and professionalization, as well as their thematic focus, and the scope of their activities, and on the broader context in terms of economic crisis, austerity policies, and political opportunities. As regards the latter, we find an impact especially on lobbying and protesting.